Platelet toll-like receptors in thromboinflammation - D'Atri, Lina Paola (2017)
Besides their undiscussed role in hemostasis and thrombosis, platelets are also key effector cells capable of assisting and modulating inflammatory reactions and immune responses. Platelets play a sentinel role in immune surveillance by recognizing danger signals from pathogens and cell damage through the expression of toll-like receptors (TLRs) on its surface and internal compartments. Platelets express all 10 TLRs transcripts and its signalosome, including adaptor proteins and transcription factors. The activation of these receptors in platelets triggers hemostatic and inflammatory responses which participate in the host’s response to bacterial and viral infections, linking thrombosis with infection and immunity. Among the responses elicited by the activation of platelet TLRs are platelet adhesion and aggregation, formation of mixed platelet-leukocyte aggregates, expression and secretion of cytokines and quemokines, and thrombin generation. TLRs also are expressed in megakaryocytes, and their activation regulates not only platelet biogenesis, but also pro-inflammatory and antiviral responses. This review will focus on work that has shown the role of platelet TLRs, mainly in thromboinflammatory responses elicited by platelets and megakaryocytes.